High prevalence of atrial fibrillation in long-term endurance cross-country skiers: echocardiographic findings and possible predictors - a 28-30 years follow-up study - Grimsmo, J.; Grundvold, I.; Maehlum, S.; Arnesen, H. (European Journal of cardiovascular prevention and rehabilitation, 2003)
Background: Lone atrial fibrillation (LAF) seems to be more common in endurance-trained male athletes than in men in the general population. The reason for this has not been found. Aim: To determine the prevalence of LAF in long-term endurance cross-country skiers and to examine possible predictors. Methods: Of 149 healthy, long-term trained cross-country skiers from three different age groups who were invited, 122 and 117 participated in the studies in 1976 and 1981, respectively. At follow-up in 2004-2006, 78 men participated, with 33 in age group I (54-62 years), 37 in group II (72-80 years) and eight in group III (87-92 years), whereas 37 individuals had died and seven could not be tracked. The examination programme applied in 1976, 1981 and 2004-2006 consisted of an electrocardiographic monitoring during rest and exercise and a maximal exercise test. Echocardiography was performed in 2004-2006. Results: A high prevalence (12.8%) of LAF was found. The only predictor from both 1976 and 1981 associated with LAF was a long PQ time (r = 0.38, P = 0.001 and r = 0.27, P = 0.02, respectively), whereas bradycardia was another predictor from 1981 (r = 0.29, P = 0.012). At follow-up, left atrial enlargement was a marker associated with LAF (P < 0.001). Conclusion: Long PQ time, bradycardia and left atrial enlargement seem to be important risk factors for LAF among long-term endurance cross-country skiers.